2016
DOI: 10.2147/rmhp.s98311
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene knowledge and practice among university students: evidence from Private Universities of Bangladesh

Abstract: Hand hygiene has achieved the reputation of being a convenient means of preventing communicable diseases. Although causal links between hand hygiene and rates of infectious disease have also been established earlier, studies focusing on hand hygiene among university-going students are not adequate in number. This study evaluated handwashing knowledge, practice, and other related factors among the selected university students in the city of Dhaka, Bangladesh. A cross-sectional study was conducted among 200 unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 21 publications
8
32
1
Order By: Relevance
“…In [16], a hand hygiene compliance rate of 17.4% amongst students was observed. A similar compliance rate of 20% for university students was established by [17], and 22.5% in another similar study by [14].…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…In [16], a hand hygiene compliance rate of 17.4% amongst students was observed. A similar compliance rate of 20% for university students was established by [17], and 22.5% in another similar study by [14].…”
Section: Introductionsupporting
confidence: 76%
“…Some previous hand hygiene studies conducted in university settings have found compliance to be generally poor [14][15][16][17]. In [16], a hand hygiene compliance rate of 17.4% amongst students was observed.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The finding of these studies was similar with the study done by Lopez-Quintero et.al (2009) on poor adherence to the constant practice of proper steps in hand washing. This study also showed that hand washing practices is low among the DM (Besha et al, 2016;Sultana, Mahumud, Sarker, & Hossain, 2016). …”
Section: Discussionsupporting
confidence: 55%
“…In the study done in Iran 65.7% participants had moderate knowledge about hand hygiene [8]. In Bangladesh study, also the knowledge about hand hygiene was not sufficient among the students and emphasized on the importance of educating students about the same [14]. Study done at Guwahati among medical and nursing students majority had good knowledge about hand hygiene and there was no statistically significant difference between them regarding knowledge [15].…”
Section: Original Research Articlementioning
confidence: 99%